Needs of the terminally ill’s relatives in palliative care: Critical review of literature - Areia, Neide P. (2017)
Terminal illness and death are critical events that interfere in the family system. The knowledge about illness and death’s impact on the family is, still, scarce. Therefore, a critical review of literature was conducted with the general goal of determining the impact of terminal illness on the family and which are the family’s support needs. The findings suggest that terminal illness is one of the most difficult experiences for the family system and an inadequate or non-existent approach to the family’s problems can put that system in risk. Therefore, palliative care aims at the integration of the family in the care plan. However, the empirical production about this topic is insufficient, which compromises the development of new efficient family approaches that are sensitive to family needs. By this way, it is important to have more research that aims to determine the family needs of terminally ill patients and develop new family intervention strategies.